Photocatalytic properties of nanostructured SrTi(1-x)Fe(x)O(3-δ) - Mohammad Ghaffari (2013)
Since 1972, titanium dioxide has been extensively investigated as a photocatalyst. Since the works of Fujishima and Honda on water-splitting using Titanium Dioxide (TiO2) and platinum electrode, dubbed the Honda-Fujishima effect, TiO2 has remained the major interest of researchers working in the field of photocatalyst. However, due to its large bandgap, pure TiO2 absorption pattern is limited to the UV region. It means TiO2 only absorbs UV light, which explains its inactivity under visible light. Thus, it is very crucial to create a visible light driven photocatalyst to increase the efficiency for solar energy or indoor light application. This study focuses on the various properties of SrTi(1-x)Fe(x)O3 nanoparticles. Different synthesis schemes were designed to produce new photocatalytic materials. Numerous techniques such as X- ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), electron microscopy both scanning (SEM) and transmission (TEM) were used for physical characterization. Photocatalytic properties were determined by the oxidation of methylene blue dye in water with results analyzed by high performance liquid chromatography (HPLC), and ultra violet - visible spectroscopy (UV-VIS).